Exploring the multi-level regulation of lignocellulases in the filamentous fungus Trichoderma guizhouense NJAU4742 from an omics perspective - Xia, Yanwei; Wang, Jingfan; Guo, Chuanxu; Xu, Huanhuan; Wang, Wei; Yang, Mingzhu; Shen, Qirong; Zhang, Ruifu; Miao, Youzhi (Microbial cell factories, 2022)
Filamentous fungi are highly efficient at deconstructing plant biomass by secreting a variety of enzymes, but the complex enzymatic regulation underlying this process is not conserved and remains unclear. In this study, cellulases and xylanases could specifically respond to Avicel- and xylan-induction, respectively, in lignocellulose-degrading strain Trichoderma guizhouense NJAU4742, however, the differentially regulated cellulases and xylanases were both under the absolute control of the same TgXyr1-mediated pathway. Further analysis showed that Avicel could specifically induce cellulase expression, which supported the existence of an unknown specific regulator of cellulases in strain NJAU4742. The xylanase secretion is very complex, GH10 endoxylanases could only be induced by Avicel, while, other major xylanases were significantly induced by both Avicel and xylan. For GH10 xylanases, an unknown specific regulator was also deduced to exist. Meanwhile, the post-transcriptional inhibition was subsequently suggested to stop the Avicel-induced xylanases secretion, which explained the specifically high xylanase activities when induced by xylan in strain NJAU4742. Additionally, an economical strategy used by strain NJAU4742 was proposed to sense the environmental lignocellulose under the carbon starvation condition, that only slightly activating 4 lignocellulose-degrading genes before largely secreting all 33 TgXyr1-controlled lignocellulases if confirming the existence of lignocellulose components. This study, aiming to explore the unknown mechanisms of plant biomass-degrading enzymes regulation through the combined omics analysis, will open directions for in-depth understanding the complex carbon utilization in filamentous fungi.